Comparison of tactical behaviour and performance of youth soccer players in 3v3 and 5v5 small-sided games - Castelao, D.; Garganta, J.; Santos, R.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2014)
Soccer is a predominantly tactical sport and tactical skills are particularly important for enhancing performance, since the actions are unpredictable, thus forcing players to constantly adapt to the situations. Our aim is to compare the tactical behaviour and performance of soccer players in 3v3 and 5v5 small-sided games (SSGs). The sample comprised 10 U-ll youth soccer players who performed 1,563 tactical actions in both 31>3and 5v5 SSGs. We used the System of tactical assessment in Soccer (FUT-SAT) to assess players' tactical behaviour and performance. Descriptive analyses were performed Shapiro- Wilk normality test was conducted T-test for repeated measures and Wilcoxon test were used to compare data between both situations (P<0.05). Significant differences were found in all categories of variables except in the category Tactical Performance Index (TPI). Players performed considerably more frequently the principles of Penetration and Delay in 3v3 and Offensive Unity and Balance in 5v5 SSGs. We concluded that while players' tactical performance has not changed, 3v3 and 5v5 demand different tactical behaviour from the players. These data can contribute to practice since coaches should take into account the changes in tactical behaviour when considering the number of players in soccer SSGs during training sessions.